Adipose tissue-derived ECM hydrogels and their use as 3D culture scaffold - Getova, Vasilena E.; van Dongen, Joris A.; Brouwer, Linda A.; Harmsen, Martin C. (Artificial cells, nanomedicine, and biotechnology, 2019)
Adipose tissue has the therapeutic capacity in the form of a fat graft, for example, for treatment of irradiation-induced scars and difficult to heal dermal wounds. For large-scale clinical application, an off-the-shelf product is warranted. In recent years, ECM-derived hydrogels are postulated to harbour therapeutic capacity and might even replicate the beneficial effects of adipose tissue. In normal homeostasis, the natural ECM acts as a deposit of growth factors, that releases them over time. In the healing of lesions, this might promote cell accumulation and proliferation which in turn stimulates angiogenesis and repair. The decellularization of tissue and the generation of hydrogels may leave cytotoxic traces. Therefore, our research assessed the cytotoxic effect of human adipose tissue-derived ECM hydrogels on connective tissue cells i.e. fibroblasts. The results showed no cytotoxicity, meaning the hydrogels caused no cell death. Cell migration and survival were observed when cultured in ECM hydrogels and followed for 7 days. Cell survival in the hydrogel was confirmed with CFDA staining and also cells showed the ability to penetrate and migrate throughout the gel. We conclude that ECM hydrogels are promising to use as innovative therapy for wound healing.